Uncertainty analysis of calibration source with adjustable degree of polarization in a wide dynamic range. (December 2021) - Kang, Qing; Liu, Zhen; Yuan, Yinlin; Zheng, Xiaobing; Li, Jianjun; Wu, Haoyu; Zhai, Wenchao
Highlights: The DoLP of APOLS is from 0 to 0.72 from 460 to 2000 nm. The major influencing systematic factors contributing to the DoLP were analyzed. The uncertainty was better than 0.5% as the DoLP of APOLS was larger than 0.26. Abstract: In order to satisfy the requirements of pre-launch laboratory calibration with high accuracy for polarization remote sensor, an innovative high precision polarimetric calibration instrument with adjustable degree of linear polarization (DoLP) in a wide dynamic range called adjustable polarization light source (APOLS) has been developed. APOLS consists of a collimated light source (CLS) and a polarization state adjuster (PSA). The PSA contains four parallel K9 glass plates, which can be orientated from 0° to 65° accurately controlled by electromechanical driving mechanism whose rotation accuracy is better than ±5″. Regarding the DoLP of APOLS, its adjustment range is from 0 to 0.72 within the spectral range from 460 to 2000 nm. The theoretical model of APOLS was established to describe the DoLP produced by multiple refraction of transmitted light. Meanwhile, the major systematic factors contributing to the DoLP uncertainty such as refractive index and absorption of K9 glass, incident angle, instability and parallelism of light source were analyzed. By using the spectro-polarimetric analyzer (SPOLA), the uncertainty evaluation experiments of APOLS were carried out. The results showed that when the DoLP value was in the range of 0.26 to 0.72, the uncertainty was less than 0.5%, and when the DoLP value was in the range of 0.003 to 0.26, the uncertainty was in the range of 8.5993% to 0.5534%. Moreover, the uncertainty was in the range of 0.0027% to 0.0032% when the uncertainty of the CLS was not considered. The consistency evaluation between APOLS and SPOLA ranged from -0.36 to 0.6 indicates the experimental results are satisfying. It can be concluded that the APOLS significantly improved the dynamic range and accuracy of the polarimetric calibration instrument.